A személyi jövedelemadózás kérdése a Bécsi Magyar Nagykövetségen foglalkoztatott munkavállalók esetében - Béres Ida Anna (2018)
The goal of this dissertation is to present the practical tax environment of the employees of the Hungarian embassy in Vienna, analyze the consequences and express an opinion. I started by studying the terminology background of tax structures while highlighting the income tax. I have presented in details the Austrian and Hungarian habits in relation the income tax. As working abroad was one of the crucial points of the subject, I have laid out an overview of the international tax agreements, points of views concerning the avoidance of double taxation, emphasizing the Hungaro-Austrian agreement and its Austrian comment. This part of the dissertation has been composed based on published articles, laws, directives, agreements and international contracts. I have presented the diplomatic institutional system, the legal status and function of embassies, I have touched on the employees of the embassies, using sources such as my several decades of experience working at an embassy and the curriculum of the mandatory exams of the Ministry of Foreign Affairs. In light of the previously mentioned topics and with the help of an external tax con-sultancy firm working with the embassy, I have analyzed the question of the personal income tax for the employees working at the embassy. As a result of the analysis – in addi-tion to the standpoint of the consulting firm – I have shown the detailed options of the local employees concerning the personal income tax, as well as my interpretation and standpoint of the situation.